Effect of adding NPK compound fertilizer and spraying with chelated iron on the growth and flowering of two cultivars of African marigold (Texas Journal of Agriculture and Biological Sciences, 2022)
The experiment was conducted for the period from 8/3/2022 to 1/8/2022, to study the effect of adding NPK compound fertilizer and chelating iron spray on the growth and flowering of two cultivars of African marigold at concentrations (0, 50 and 100) mg.L-1 , the second factor: spraying with chelated iron at concentrations (0, 25 and 50), the third factor: two cultivars of the African marigold Taishan (orange) and Taishan (yellow), the results of the experiment showed as follows: The cultivar Taishan (orange) in most of the vegetative and flowering characteristics of the African marigold outperformed the cultivar Taishan (yellow), as it recorded the highest values for plant height (29.73) cm, number of leaves (34.14) leaf-1 , and number of petals in the flowering inflorescence (193.03). Flower petal-1, inflorescence diameter 61.96 mm, total carotenoids content in inflorescences (0.17) mg 100 g dry weight.